Pengaruh Efektivitas Dana Pihak Ketiga, Resiko Pembiayaan, Rasio Efisiensi, dan Kecukupan Modal Terhadap Profit Distribution Management Bank Umum Syariah di Indonesia Periode (2017-2020) - Carisa, Mela (Institut Agama Islam Negeri Metro, 2023)
This research is a quantitative study with a correlational approach, focusing on Islamic commercial banks in Indonesia registered with the Financial Services Authority (OJK). The sampling method used was purposive sampling, selecting 11 Islamic commercial banks in Indonesia as the sample. The study employs secondary data obtained from quarterly financial reports covering the period from the first quarter of 2017 to the third quarter of 2020. Data analysis is conducted using panel data regression with EViews 10 software. The findings reveal that capital adequacy, the effectiveness of third-party funds, financing risk, and efficiency ratios collectively influence the profit distribution management of Islamic commercial banks in Indonesia for the 2017-2020 period. Specifically, capital adequacy and efficiency ratios have a positive effect on profit distribution management, while the effectiveness of third-party funds and financing risk have a negative effect. The coefficient of determination test shows that these variables collectively explain 99.9% of the variation in profit distribution management.